2013
DOI: 10.1128/jb.00715-13
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Activities of Streptococcus pneumoniae Serotype 2 Capsular Glycosyltransferases and Significance of Suppressor Mutations Affecting the Initiating Glycosyltransferase Cps2E

Abstract: The capsular polysaccharide (CPS) is essential for Streptococcus pneumoniae virulence. Its synthesis requires multiple enzymes, and defects that block completion of the pathway can be lethal in the absence of secondary suppressor mutations. In this study, we examined the functions of three capsular glycosyltransferases (Cps2F, Cps2G, and Cps2I) involved in serotype 2 CPS synthesis, whose deletions select for secondary mutations. We demonstrate that Cps2F is a rhamnosyltransferase that catalyzes addition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…However, it is still incompletely understood how this is accomplished: a phosphorelay system comprised of CpsB, CpsC, and CpsD and transcriptional regulation of capsule genes comprise two levels of control of capsule levels (33-35, 62, 63). This study and work by others supports the notion that there exists another potential layer of control, involving mutations in the gene encoding the initiating glycosyltransferase, cpsE (39,40). Our experiments using serotype-matched acapsular and encapsulated conjunctival isolates support the idea that this level of control occurs in nature.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…However, it is still incompletely understood how this is accomplished: a phosphorelay system comprised of CpsB, CpsC, and CpsD and transcriptional regulation of capsule genes comprise two levels of control of capsule levels (33-35, 62, 63). This study and work by others supports the notion that there exists another potential layer of control, involving mutations in the gene encoding the initiating glycosyltransferase, cpsE (39,40). Our experiments using serotype-matched acapsular and encapsulated conjunctival isolates support the idea that this level of control occurs in nature.…”
Section: Discussionsupporting
confidence: 75%
“…The two colony types were genetically stable, yielding high and low capsule expression, respectively, for the opaque and transparent types (data not shown). Since mutations in the cpsE gene, which encodes the initiating glycosyltransferase (38), were reported to result in a reduction of capsule expression (39,41,42), we sequenced this gene in both transparent and opaque variants. These data revealed that, while the opaque strain had a wild-type cps4E sequence, the transparent variant possessed a duplication of a 6-nucleotide sequence, GCGATT, which results in the addition of an alanine and isoleucine after amino acid 45 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Paired with genetic studies, studies on capsular synthesis have shown that the synthetic machinery is fairly sensitive to mutation inasmuch as mutations resulting in incomplete or dramatically altered repeat units are not compatible with the flippase/polymerase and are lethal to the organism, presumably due to the sequestration of undecaprenyl phosphate acceptor (79,80).…”
Section: Genetic and Biochemical Bases Of Capsular Synthesismentioning
confidence: 99%